Modulators of cytoskeletal reorganization in CA1 hippocampal neurons show increased expression in patients at mid-stage Alzheimer's disease. - Patricia F Kao (Public Library of Science (PLoS), 2010)
During the progression of Alzheimer's disease (AD), hippocampal neurons undergo cytoskeletal reorganization, resulting in degenerative as well as regenerative changes. As neurofibrillary tangles form and dystrophic neurites appear, sprouting neuronal processes with growth cones emerge. Actin and tubulin are indispensable for normal neurite development and regenerative responses to injury and neurodegenerative stimuli. We have previously shown that actin capping protein beta2 subunit, Capzb2, binds tubulin and, in the presence of tau, affects microtubule polymerization necessary for neurite outgrowth and normal growth cone morphology. Accordingly, Capzb2 silencing in hippocampal neurons resulted in short, dystrophic neurites, seen in neurodegenerative diseases including AD. Here we demonstrate the statistically significant increase in the Capzb2 expression in the postmortem hippocampi in persons at mid-stage, Braak and Braak stage (BB) III-IV, non-familial AD in comparison to controls. The dynamics of Capzb2 expression in progressive AD stages cannot be attributed to reactive astrocytosis. Moreover, the increased expression of Capzb2 mRNA in CA1 pyramidal neurons in AD BB III-IV is accompanied by an increased mRNA expression of brain derived neurotrophic factor (BDNF) receptor tyrosine kinase B (TrkB), mediator of synaptic plasticity in hippocampal neurons. Thus, the up-regulation of Capzb2 and TrkB may reflect cytoskeletal reorganization and/or regenerative response occurring in hippocampal CA1 neurons at a specific stage of AD progression.